Magnetization dating at a medieval monastery (Tupholme, Lincolnshire) - Borradaile, Graham John (Archaeometry, 1999)
Keywords: tupholme

The 'White Canons' Rediscovered: clearance work at Tupholme Abbey - Bainbridge, Norman (History Today, 1990)
Norman Bainbridge on springtime for Tupholme Abbey.
Keywords: tupholme